Effector-specific priming effects during action observation in combat sports - Polzien, A.; Güldenpenning, I.; Weigelt, M. (German Journal of Exercise and Sport Research, 2019)
The anticipation of actions of other individuals is crucial for skilled performance. A possible mechanism that could enable the anticipation of action is that of action simulation. We conducted three experiments to investigate effector matching processes, which are thought to be a basic prerequisite for action simulation during action observation. To this end, a static picture of a combat sport athlete performing a kick or a punch was presented. Participants were instructed to respond to a colored target, by either pressing a hand or a foot button. In congruent conditions, the effector in the picture (i.e., the hand during the punch and the foot during the kick) and the participants` responding effector (i.e., the hand or foot) were the same, whereas in incongruent conditions, they differed. In Experiment 1, the colored target consisted of a blue or red frame surrounding the picture. When participants responded to the frame`s color, the task-irrelevant action displayed in the picture did not induce any effector-specific priming effects. In Experiment 2, a colored circle surrounded the active or passive effector in the picture. When the attention was directed to the effector, participants showed faster reactions and fewer errors in congruent compared to incongruent conditions, regardless of whether the circle surrounded the active or passive effector. Experiment 3 verified that the results found in Experiment 2 were based on effector matching rather than on a spatial feature overlap between stimulus and response. Different underlying mechanisms regarding the priming processes during action observation are discussed.